Find the positive constant C such that
C = x ≥ 0 , x y = C max x y
Bonus:
Can you figure out
x
≥
0
,
x
y
=
N
max
x
y
?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
But for x=y=2 we get c=4 that is larger than e!!
Log in to reply
What about e 4 / e ? ;) The result means that the maximum value will always be e c / e , not necessarily equal to e (only in the given case).
same i have done..
Relevant wiki: Lagrange Multipliers
We will use Lagrange Multipliers to solve this problem. Namely, we will find the maximum of the general case, and then set this general case to be equal to c , and solve.
The Lagrangian of the given is L = x y − λ ( x y − c ) We set the gradient of this to be the zero vector, namely ∇ L = ⎣ ⎡ ∂ x ∂ L ∂ y ∂ L ∂ λ ∂ L ⎦ ⎤ = ⎣ ⎡ y x y − 1 − λ y x y ln ( x ) − λ x x y − c ⎦ ⎤ = ⎣ ⎡ 0 0 0 ⎦ ⎤ Now we have a system of equations, namely ⎩ ⎪ ⎨ ⎪ ⎧ y x y − 1 = λ y x y ln ( x ) = λ x x y = c The third equation is simply the constraint, so we focus on the first and second equation. Divide the first equation by y and the second equation by x (we can do this because x , y = 0 ) to get that { x y − 1 = λ x y − 1 ln ( x ) = λ ⟹ ln x = 1 ⟹ x = e Thus, the maximal pair is ( x , y ) = ( e , c / e ) and max ( x y ) = e e c We set this to equal c to get that e e c = c ⟹ e c = c e Obviously, the only positive solution to this is that c = e ≈ 2.718 and we are done.
Nicely presented!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Extrema - Problem Solving - Medium
f ( x , y ) = x y
f ( x ) = x x c = ( x x 1 ) c
This is maximized when x x 1 is maximized.
g ( x ) = x x 1
g ′ ( x ) = x x 1 ( x 2 1 − x 2 ln ( x ) )
g ′ ( x ) = 0 → ln ( x ) = 1 , x = e
x → e − lim g ′ ( x ) > 0
x → e + lim g ′ ( x ) < 0
Thus x = e is a point of local maxima.
g ( x ) m a x = e e 1
f ( x ) m a x = e e c
e e c = c
e c = c e
Drawing the graph we can see that there's only one positive solution c = e